Nanoprobes to investigate nonspecific interactions in lipid bilayers: from defect-mediated adhesion to membrane disruption. Issue 17 (30th July 2021) - Razza, Nicolò; Lavino, Alessio D.; Fadda, Giulia; Lairez, Didier; Impagnatiello, Andrea; Marchisio, Daniele; Sangermano, Marco; Rizza, Giancarlo
Abstract : When a lipid membrane approaches a material/nanomaterial, nonspecific interaction may occur. The interplay between electrostatic and hydrophobic interactions determines the existence of a thermodynamic optimum for the membrane structural integrity. Abstract : When a lipid membrane approaches a material/nanomaterial, nonspecific adhesion may occur. The interactions responsible for nonspecific adhesion can either preserve the membrane integrity or lead to its disruption. Despite the importance of the phenomenon, there is still a lack of clear understanding of how and why nonspecific adhesion may originate different resulting scenarios and how these interaction scenarios can be investigated. This work aims at bridging this gap by investigating the role of the interplay between cationic electrostatic and hydrophobic interactions in modulating the membrane stability during nonspecific adhesion phenomena. Here, the stability of the membrane has been studied employing anisotropic nanoprobes in zwitterionic lipid membranes with the support of coarse-grained molecular dynamics simulations to interpret the experimental observations. Lipid membrane electrical measurements and nanoscale visualization in combination with molecular dynamics simulations revealed the phenomena driving nonspecific adhesion. Any interaction with the lipidic bilayer is defect-mediated involving cationic electrostatically driven lipid extraction and hydrophobically-driven chain protrusion, whose interplay determines the existence of a thermodynamic optimum for the membrane structural integrity. These findings unlock unexplored routes to exploit nonspecific adhesion in lipid membranes. The proposed platform can act as a straightforward probing tool to locally investigate interactions between synthetic materials and lipid membranes for the design of antibacterials, antivirals, and scaffolds for tissue engineering.